Delegations during the time of the prophet, peace and blessings be upon him, as described in Ibn Abd Rabbihs book, AL Iqd al Farid ـــ Historical Study ـــ - Hazem, Raghad Thawban; Allah , Nidal Muayyad Mal (Academia Open, 2026)
General Background: The Prophetic biography provides key insights into the formation of the early Islamic state. Specific Background: Al-Iqd al-Farid by Ibn Abd Rabbih records the delegations that visited the Prophet Muhammad (PBUH) during the Year of Delegations. Knowledge Gap: The historical significance of these accounts has received less attention than the book’s literary value. Aims: This study analyzes the delegations narrated in Al-Iqd al-Farid using a historical analytical approach. Results: The findings show that these delegations involved dialogue, written agreements, and legislative arrangements that facilitated tribal integration into the Islamic state. The narratives also highlight the use of poetry and oratory in expressing loyalty and political affiliation. Novelty: This study demonstrates the dual literary and historical value of Al-Iqd al-Farid in documenting Prophetic diplomacy. Implications: The research contributes to understanding early Islamic governance, diplomatic communication, and social cohesion. Highlights: • Al-Iqd al-Farid documents tribal negotiations and written agreements during the Year of Delegations.• Prophetic leadership applied dialogue, covenant, and administrative regulation in integrating Arab tribes.• Literary narration and historical reporting were combined to preserve accounts of early Islamic governance. Keywords: Prophetic Delegations, Al Iqd Al Farid, Early Islamic State, Prophetic Diplomacy, Islamic Governance